Talag-Bahay an autonomy-generative healthcare living lab centering on the research of co-designed domotic apartments - Flordeliz, Alexandria Kiara M.
Independent living is a continuing challenge for persons with mobility, visual, and/or auditory functional difficulty as there is a lack of effort geared towards the design of living spaces that mitigate the challenges attached to it, especially within the Philippine context. To raise the degree of autonomy felt by this population as they accomplish day-to-day activities at home, a space dedicated to the research of accessible, smart living spaces is then necessitated. This shall be addressed through a Healthcare Living Lab, an open innovation approach to a research center that facilitates co-design and works within the paradigm of healthcare. As such, the overarching goal of this study is to design an autonomy-generative Healthcare Living Lab centering on the research of co-designed Domotic Apartments. Integrating research into the dimension of healthcare, this architectural project is argued to raise the degree of autonomy experienced by persons with mobility, vision, and hearing impairments as they perform basic activities of daily living tasks thereby promoting independent living.